Eficacia de la estrategia de control del ritmo en pacientes con miocardiopatía hipertrófica y fibrilación o flutter auricular sometidos a cardioversión eléctrica - R Egas, Diego (2017)
Background: fibrillation and atrial flutter are frequent arrhythmias in patients with hypertrophic cardiomyopathy and increase their morbidity. Cardioversion of arrhythmia improves the quality of life of the patient; however, there is no information on the efficacy or predictors of this therapy in the literature.Aim: to identify the variables related to the evolution of the arrhythmia after therapy in patients with hypertrophic cardiomyopathy associated with atrial fibrillation or flutter were underwent electrical cardioversion.Methods: data from 37 patients with atrophic cardiomyopathy associated with atrial fibrillation (n = 21) and atrial flutter (n = 16), submitted to electrical cardioversion, were analyzed for immediate success (reversion after shock), Recurrence (recurrence of the problem after electrical cardioversion) and late success (sinus rhythm observed at the last recorded visit).Results: immediate success occurred in 96% of electrical cardioversion procedures in patients with atrial fibrillation and in 100% of patients with atrial flutter. Recurrence occurred in 76.9% of patients with atrial fibrillation who underwent electrical cardioversion after an average time of 630 days and in 57.1% of patients with atrial flutter after a follow-up of 1,138 days.Conclusion: the efficacy of electrical cardioversion was evaluated, by the clinical results observed in patients with hypertrophic cardiomyopathy associated with atrial fibrillation or flutter; in addition, variables related to recurrence and late success after electrical cardioversion, were identified.